PENEGAKAN HUKUM TERHADAP KASUS KORUPSI PT. TIMAH SEBAGAI BENTUK POTRET BURUK TATA KELOLA SEKTOR EKSTRAKTIF - Heni Marlina; Aprita, Serlika (The Juris, 2024)
Corruption is one of the social diseases that is the same as other types of crimes such as theft. The problem is that corruption is increasing along with the progress of prosperity and technology. As happened in the case of the tin corruption crime committed by Harvey Mois, where the nominal state loss was also not small, estimated at IDR 271 trillion. This research method uses a normative legal research type, a legal research method carried out by examining library materials or secondary data. This case is suspected to have occurred in the period 2015-2020. Harvey Mois has an important role in this case, namely as an intermediary for other perpetrators. In this case, he became a representative of PT Refined Bangka Tin (RBT) in a case with PT Timah regarding illegal mining activities in the IUP Persero area. The articles charged to the suspect are Article 2 paragraph (1) and Article 3 in conjunction with Article 18 of Law of the Republic of Indonesia Number 31 of 1999 as amended and supplemented by Law Number 20 of 2001 in conjunction with Law of the Republic of Indonesia Number 31 of 1999 concerning Amendments to Law of the Republic of Indonesia Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption in conjunction with Article 55 paragraph (1) ke-1 of the Criminal Code. The ’mass’ corruption case resulted in environmental losses of up to Rp 271,069,688,018,700 or Rp 271 trillion, and a total of 16 suspects have been detained by the Attorney General’s Office.